A pH-sensitive fluorescent protein sensor to follow the pathway of calcium phosphate nanoparticles into cells. (15th July 2020) - Kollenda, Sebastian; Kopp, Mathis; Wens, Jasmin; Koch, Johannes; Schulze, Nina; Papadopoulos, Chrisovalantis; Pöhler, Robert; Meyer, Hemmo; Epple, Matthias
Abstract: Calcium phosphate nanoparticles (100 nm) were fluorescently labelled with poly(ethyleneimine) (PEIATTO490LS ; red fluorescence). They were loaded with a Tandem fusion protein consisting of mRFP1-eGFP (red and green fluorescence in the same molecule)that acts as smart biological pH sensor to trace nanoparticles inside cells. Its fluorescence is also coupled to the structural integrity of the protein, i.e. it is also a label for a successful delivery of a functional protein into the cell. At pH 7.4, the fluorescence of both proteins (red and green) is detectable. At a pH of 4.5-5 inside the lysosomes, the green fluorescence is quenched due to the protonation of the eGFP chromophore, but the pH-independent red fluorescence of mRFP1 remains. The nanoparticles were taken up by cells (cell lines: HeLa, Caco-2 and A549) via endocytic pathways and then directed to lysosomes. Time-resolved confocal laser scanning microscopy confirmed mRFP1 and nanoparticles co-localizing with lysosomes. The fluorescence of eGFP was only detectable outside lysosomes, i.e. most likely inside early endosomes or at the cell membrane during the uptake, indicating the neutral pH at these locations. The Tandem fusion protein provides a versatile platform to follow the intracellular pathway of bioactive nanocarriers, e.g. therapeutic proteins. The transfection with a Tandem-encoding plasmid by calcium phosphate nanoparticles led to an even intracellular protein distribution in cytosol and nucleoplasm, i.e. very different from direct protein uptake. Neither dissolved protein nor dissolved plasmid DNA were taken up by the cells, underscoring the necessity for a suitable carrier like a nanoparticle. Statement of Significance: A pH-sensitive protein ("tandem") was used to follow the pathway of calcium phosphate nanoparticles. This protein consists of a pH-sensitive fluorophore (eGFP; green) and a pH-independent fluorophore (mRFP1; red). This permits to follow the pathway of a nanoparticle inside a cell. At a low pH inside an endolysosome, the green fluorescence vanishes but the red fluorescence persists. This is also a very useful model for the delivery of therapeutic proteins into cells. The delivery by nanoparticles was compared with the protein expression after cell transfection with plasmid DNA encoding for the tandem protein. High-resolution image analysis gave quantitative data on the intracellular protein distribution. Graphical Abstract: Image, graphical abstract